MODERATE EDUCATION: Overcoming Juvenile Delinquency through the Implementation of Pesantren Character Education in Darul Ulum Waru Sidoarjo Junior High School - Muh Furqon; M. Amin Afandi; M. Arif Rifa'i; Saifulloh Umar; Moh. Ismail (Journal Multicultural of Islamic Education, 2023)
This scientific abstract explores the efficacy of addressing juvenile delinquency through the implementation of Pesantren Character Education at Darul Ulum Waru Sidoarjo Junior High School. The study delves into the integrated approach of infusing moral and ethical teachings into academic subjects, as well as the emphasis on core values such as empathy, humility, and respect. Through qualitative analysis and insights from educators Darul Ulum Waru Sidoarjo Junior High School, the research demonstrates the significance of these educational strategies in shaping the character of students. By examining the impact on holistic development, the abstract contributes valuable insights into the potential of Pesantren Character Education as a preventive measure against juvenile delinquency, providing a scientific foundation for educators, policymakers, and researchers.